Development of a contextual-based chemistry e-module on electrolyte and non-electrolyte solutions for high school students - Hasna, Hasna; Laksmiwati, Dwi; Hadisaputra, Saprizal; Muti’ah, Muti’ah (Chemistry Education Practice, 2023)
This study aims to produce a chemistry e-module on electrolyte and non-electrolyte solutions for high school students. This study uses a research and development model grouped into three parts: preliminary studies, initial product development, and evaluation. The total population of the study was 144 students of SMA NW Suralaga, with 40 grade 11 students as the sample. Data collection techniques using a questionnaire then analyzed descriptive statistics. The results showed that (1) the results of the chemical e-module validation analysis were included in the very valid category (0.825). (2) the results of the analysis of student responses to the chemistry e-module fall into the very practical category (84%).